Pengertian dan Makna Sekularisasi - Mardinal Tarigan; Lutfi Putri Khairani; Sonia Sabilla; Liyundzira Fikrih Gani; Khoiriyah Sari (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Recently, the theory of secularization has been hot and hotly discussed again, this is part of the increasing political influence of mass organizations and religious movements in various places. Like the Christian right in North America, Jewish fundamentalism in Israel, fundamentalism in India and Islamic fundamentalism in many countries, one of which is Europe. This is also related to the increasing willingness of a person to various kinds of spirituality, such as New Age, which is not the same as the old forms of formal religion. All these advances undermine not only the basic assumptions of secularization theory, which shows the declining role of religion in modern times, but also the old formulation of the separation of church and state. These are the times when Nancy Robsenblum’s use of “civic obligations” is increasingly displaced by “demands of faith”.